Born to win - Passer, Ivan; Milton, David Scott, 1934-; Segal, George, 1924-2000; Prentiss, Paula, 1939-; Black, Karen, 1939-2013; Theatre Guild; Segal-Tokofsky Productions Inc.; Cinetel Films ([New York, NY] : Theater Guild : Segal-Tokofsky Productions Inc., 1971)
George Segal plays Jay Jay, an ex-hairdresser who struggles to support his expensive drug habit. To avoid arrest, Jay Jay turns "narc," informing on his fellow junkies. Eventually Jay Jay's sense of self-hatred threatens to overwhelm him. --
Originally released as motion picture in 1971.
Movie distributed by Cinetel for Digitalia Film Library.
George Segal, Paula Prentiss, Jay Fletcher, Hector Elizondo, Karen Black.
Directors of photography, Jack Priestley, Richard Kratina; editor, Ralph Rosenblum; music, William S. Fischer.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 31, 2015)
Keywords: Drug addicts -- Drama; Drug traffic -- Drama; Detective and mystery films; Crime films; Feature films; Internet videos; Streaming video